RESPONSE OF MAIZE (ZEA MAYS L.) TO RATES OF NITROGEN AND ZINC APPLICATION IN MINNA, SOUTHERN GUINEA SAVANNA OF NIGERIA. - Afolabi, Saheed G. (Journal of Agricultural Sciences (Belgrade), 2019)
Field experiment was conducted in 2014 and 2015 cropping seasons at the Teaching and Research Farm of the Federal University of Technology, Minna to evaluate the effects of different rates of nitrogen (N) and zinc (Zn) on the growth and yield of maize. The treatments were four levels of N; 0, 60, 90 and 120 kg ha-1 and three levels of Zn; 0, 2.5 and 5 kg ha-1. The experimental design was a 4 × 3 factorial fitted in a randomised complete block design with three replications. The soil was relatively low in initial N content and relatively high in soil extractable Zn of 2.30 mg kg-1. The main effect of N on the growth of maize was significant (p<0.05) only at 8 weeks after sowing (WAS) in 2014 and 8 and 12 WAS in 2015. In 2014, the interaction effect of N and Zn on growth of maize plant was only significant (p<0.05) at 8 WAS in both seasons. The treatments without N produced the lowest grain and stover yields. There was a significant (p<0.05) response to N fertilization on grain yield in both seasons. The main effects of Zn on both stover and grain yield were only significant in 2015. The interaction effects of both N and Zn on stover and grain yield of maize were not significant in both seasons. Nitrogen rate of 60 kg N ha-1 with 2.5 kg Zn ha-1 was optimum for maize production in Minna, Nigeria.